Flavor Aspects of Pulse Ingredients. Issue 1 (5th October 2016) - Roland, Wibke S. U.; Pouvreau, Laurice; Curran, Julianne; van de Velde, Fred; de Kok, Peter M. T.
Abstract : Pulses (Fabaceae) have regained interest for their high protein level. However, food application of pulses and pulse ingredients is hampered by several issues around their off‐flavor. Off‐flavors in pulses are partially inherent and partially produced during harvesting, processing, and storage. Generally, volatile off‐flavor compounds in pulses belong to the categories of aldehydes, alcohols, ketones, acids, pyrazines, sulfur compounds, and others, and off‐taste is strongly correlated to the presence of saponins, phenolic compounds, and sometimes alkaloids. No systematic studies have been performed on the identification of the off‐flavor compounds present in pulses in relation to their contribution to the overall perception of the pulses. This review article aims to provide a concise overview highlighting the most important aspects of the knowledge available on the off‐flavor compounds present in various pulses, their possible origins, and the technologies available to prevent, reduce, or mask these off‐flavor compounds. Rather than attempting to make a full inventory of the literature in the field, this paper addresses the most relevant topics referring to a selected set of relevant papers on each topic to substantiate the observations and conclusions that may guide the reader toward additional literature.